Health Workers' Behavior and Attitudes: Impact on ARV Medication Adherence - Idawati Manurung; Yuliati Amperaningsih; El Rahmayati (Universitas Malahayati Lampung, 2025)
ABSTRACT Loss to follow-up in antiretroviral therapy (ART) is a frequent issue for people living with HIV (PLHIV), accelerating disease progression to AIDS and increasing HIV transmission rates. To address this, this study evaluated the influence of health workers' behavior and attitudes on ART adherence by examining PLHIV's perceptions of their conduct and perspectives during service delivery. A quantitative descriptive study employing questionnaires was conducted with a convenience sample of 42 people living with HIV (PLHIV) from a population of 200 individuals actively receiving antiretroviral therapy (ART) between April and June 2024. The study found that most participants were adult males diagnosed with HIV within the past two years and had a history of loss to follow-up. While participants generally reported positive perceptions of health workers' behavior and attitudes, and indicated high adherence to ART, statistical analysis showed no significant relationship between perceived health worker behavior and adherence. However, a significant relationship was found between positive perceptions of health worker attitudes and ART adherence. In conclusion, despite positive perceptions of health workers' behavior and attitudes among PLHIV in Bandar Lampung, ART adherence remains a concern, suggesting the need for targeted training in communication and counseling for health workers to enhance adherence potentially. Keywords: HIV Patients, Behavior, Attitudes, Adherence.